Diagnosis of Bovine Digital Dermatitis: Exploring the Usefulness of Indirect ELISA - Afonso, João Sucena; Oikonomou, Georgios; Carter, Stuart; Clough, Helen E.; Griffiths, Bethany E.; Rushton, Jonathan (Frontiers in Veterinary Science, 2021)
The precision by which animal diseases are diagnosed affects our ability to make informed decisions with regards to animal health management, from a clinical and economic perspective. Lameness is a major health condition in dairy cattle. The underlying causes of lameness include bovine digital dermatitis (BDD), which is reported as one of the main causes of infectious lameness in dairy cattle. Presently, the gold standard for BDD diagnosis in dairy cattle is visual inspection of lifted hooves – a labour intensive and subjective method. Research has suggested that Treponema spp. are the main pathogens associated with the establishment of BDD. We explored the potential of indirect enzyme-linked immunosorbent assay (ELISA) as a diagnostic serological tool in the identification of cows at different stages of BDD. Additionally, we evaluated the predictive power of this diagnostic tool on the future occurrence of BDD lesions. A total of 232 cows from three farms were used in the study. Serum samples and hoof-health data were collected at three time points: approximately 30 days pre-calving, around calving and approximately 30 days post-calving. The mean absorbance from the ELISA test was compared across the different clinical presentations of BDD as assessed by visual inspection of the hooves according to the M-stage classification system. A transition model was developed to estimate the probability of lesion occurrence in time t+1 based on the spectrophotometer (absorbance) reading in time t. The mean absorbance reading for both IgG1 and IgG2 anti-Treponema antibodies was associated with disease presence – apart from M4.1 lesions, animals with no lesions had a lower mean when compared to animals with lesions regardless of the score. Additionally, the mean absorbance reading of animals with active lesions was higher when compared to animals with no lesions. However, the anti-Treponema antibody assays failed to identify disease presence in a consistent manner. Moreover, indirect ELISA readings were not a predictor of the future occurrence of BDD lesions. In conclusion, although the levels anti-Treponema antibodies were associated with disease presence, the ELISA test failed to detect disease unequivocally, and had no predictive value in the future occurrence of BDD lesions.